Psychosocial Risk Factors Related with Cardiovascular Disease in Pakistani Population - Asfandyar, Zubaida Mujtaba, Abdul Wadood Kakar, Aqeel Ahmad, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To enlist the psychosocial risk factors related with cardiovascular disease. Study design: Prospective study Place and duration of study: Department of Cardiology, Loralai Medical College & Hospital, Loralai from 1st January 2021 to 30th June 2021. Methodology: One hundred and twenty patients of cardiovascular diseases were enrolled. Through a well-structured questionnaire psychosocial stress was measured in terms of grading’s and scores. Socio-demographic details were recorded. Results: The majority of patients were females with a mean age of the patients were 54.2±4.5 years. Stress level for the loss of loved ones at moderate grade was 56.6% and severe stress by37.5% of patients for the same. There were 13.3% widow or divorced who felt severe stress related to their marital status and 58% had low grade stress associated with their job. Conclusion: Loss of loved ones, marital stress, financial and job related stress are the main psychosocial factors identified as major risk of cardiovascular disease.